Enhancing chemistry learning for secondary school’s students using virtual reality / Muhammad Nabil Shah Zafarin … [et al.] - Zafarin, Muhammad Nabil Shah; Chiou Sheng, Chew; Ahmad Fesol, Siti Feirusz; Tse Guan, Tan; Kim On, Chin (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Traditional methods of teaching chemistry in secondary schools have proven to be less effective in engaging students and facilitating a deep understanding of scientific concepts throughout the years. Moreover, conducting experiments in a physical setting is limited due to potential costs and safety risks for students. This study aims to enhance the learning process through the development of a virtual reality chemistry learning application called VRChemEd application. VRChemEd application aims to enhance the learning experience for secondary school students by providing immersive and interactive visualization of chemical reactions, resulting in better comprehension of complex concepts. By leveraging the Simulation-Based Edutainment Model within the Analyze, Design, Develop, Implement, and Evaluate methodology, the application offers personalized learning experiences, and self-paced learning education. A usability evaluation was conducted to measure the effectiveness of a VRChemEd application in improving chemistry education. The results are positive, with an average score of 91.25% on the System Usability Score questionnaire. Future work will aim to improve the VRChemEd application by adding realistic simulations, multiplayer capabilities, and enhanced physics realism to enhance its impact and commercial viability.